Different effects of a perioperative single dose of dexamethasone on wound healing in mice with or without sepsis - Chen, Yuanyang; Chen, Xiaoshan; Zhou, Quanhong (Frontiers in Surgery, 2023)
Sepsis delays wound healing owing to uncontrolled inflammation. A single perioperative dose of dexamethasone is widely used because of its anti-inflammatory effects. However, the effects of dexamethasone on wound healing in sepsis remain unclear. Here, we discuss the methods to obtain dose curves and explore the safe dosage range for wound healing in mice with or without sepsis, from 0.121 to 2.03 mg/kg and from 0 to 0.633 mg/kg, respectively. Using image records, immunofluorescence, and histological staining, we found that a single dose of dexamethasone (1 mg/kg, i.p.) promoted wound healing in septic mice, but delayed wound healing in normal mice. We examined inflammatory cytokines and M1/M2 macrophages in the wound bed. In normal mice, dexamethasone delays inflammation, resulting in an insufficient number of macrophages during the healing process. In septic mice, dexamethasone alleviated excessive inflammation and maintained the balance of M1/M2 macrophages in the early and late healing process. In summary, the safe dosage range of dexamethasone in septic mice is wider than that in normal mice. A single dose of dexamethasone (1 mg/kg) increased wound healing in septic mice, but delayed it in normal mice. Our findings provide helpful suggestions for the rational use of dexamethasone.